2022
DOI: 10.1155/2022/8184534
|View full text |Cite
|
Sign up to set email alerts
|

Biophilic Design as an Important Bridge for Sustainable Interaction between Humans and the Environment: Based on Practice in Chinese Healthcare Space

Abstract: Since the COVID-19 epidemic, there has been an increased need for well-being and sustainable development, making biophilic design in hospital environments even more significant. However, after investigation, it was found that in many countries including China, the biophilic design of some hospitals is seriously absent, while other parts have the integration of biophilic design, but the standardization and recognition are not high. By restoring the interaction between buildings and nature, biophilic design impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…In addition, indoor plants can reduce stress and increase pain tolerance [51]. The positive impact of biophilic design patterns in healthcare spaces has been studied, showing that direct experience of nature is more effective than simulated natural analogues [62].…”
Section: 5e Contradictionsmentioning
confidence: 99%
“…In addition, indoor plants can reduce stress and increase pain tolerance [51]. The positive impact of biophilic design patterns in healthcare spaces has been studied, showing that direct experience of nature is more effective than simulated natural analogues [62].…”
Section: 5e Contradictionsmentioning
confidence: 99%
“…Com a finalidade de contextualizar os conceitos do design biofílico e como são aplicados principalmente na arquitetura hospitalar, foram selecionadas primeiramente publicações referência na área de estudo do Design Biofílico (KELLERT; CALABRESE, 2015;WILSON, 1984;ZHAO;ZHAN;XU, 2022;TEKIN;CORCORAN;GUTIÉRREZ, 2022). Essas publicações serviram para definir o protocolo de pesquisa, identificando as palavras-chave, definindo os objetivos e contextualizando as perguntas que orientaram a RSL.…”
Section: Etapa 1 -Planejamento Da Pesquisa E Definição Do Protocolo D...unclassified
“…The benefits of biophilic design include a greater connection to nature that has the potential to enhance well-being and productivity, reduce stress and promote creativity and learning. In healthcare settings, it has been found to be beneficial (Zhao et al 2022). A study from the University of Oregon found that some employee absences could be attributed to office environments that lacked a view of nature (Elzeyadi 2011).…”
Section: Biophilia and Biophilic Designmentioning
confidence: 99%